(untitled) (Research, Society and Development, 2020)
Introduction: stress is one of the risk factors for hypertension, and among the benefits of practicing yoga is its reduction, as well as the increase in the ability to concentrate and creativity, the balance of sleep, the promotion of mental re-education, among others, providing quality of life. In addition, the National Policy of Integrative and Complementary Practices in Brazil, aimed at preventing diseases and promoting health. Objective: to identify the scientific evidence on the practice of yoga in the treatment of hypertensive patients. Methodology: this is an integrative review about yoga as a complementary health practice for hypertension. The search was carried out by consulting scientific articles from March to July 2019 in electronic databases, including articles published in full between the years 2013 and 2019. Results: of the 279 studies initially identified, only seven publications composes this review, involving a total of 508 patients, who participated in the majority of randomized clinical studies. Conclusion: studies show that the practice of yoga by hypertensive patients as a complementary practice brings evidence of effectiveness.